Nutritional supplement-usage associated characteristics of high-performing athletes. Issue 1 (4th January 2016) - Sousa, Mónica; Fernandes, Maria João; Soares, José; Moreira, Pedro; Teixeira, Vítor Hugo
Abstract : Purpose: – The purpose of this paper is to analyse differences in sociodemographic and sporting characteristics, health-behaviours, and food intake of athletes using and not using nutritional supplements (NS). Design/methodology/approach: – High-performance Portuguese athletes from 13 sports completed a NS usage questionnaire, assessing information on sociodemographic (sex, age, height, weight, athlete's, and parental education level), health-related (smoking, daily time of sleeping, walking, and sitting), and sporting (type, number of international performances, weekly hours of training and weekly hours of gym) characteristics; and a semi-quantitative food-frequency questionnaire (86 items), regarding the previous 12 months. Findings: – From the 241 athletes (66 per cent males, 13-37 years), 64 per cent reported NS use. Supplement usage was associated with age 18 years (odds ratio (OR) 2.57, 95 per cent; confidence interval (CI) 1.17-5.65), performing individual sports (OR 5.45, 95 per cent; CI 2.49-11.93) and > 2 h gym/week (OR 2.42, 95 per cent; CI 1.15-5.11), a higher consumption of meat (OR 2.83, 95 per cent; CI 1.36-5.90), eggs (OR 2.53, 95 per cent; CI 1.07-5.96), and yogurt (OR 2.24, 95 per cent; CI 1.08-4.62), and a lower intake of processed meat (OR 0.32, 95 per cent; CI 0.15-0.72), vegetable oils (OR 0.35, 95 per cent; CI 0.17-0.74), margarine (OR 0.37, 95 per cent; CI 0.18-0.76), chips (OR 0.22, 95 per cent; CI 0.10-0.48), and fast food (OR 0.42, 95 per cent; CI 0.19-0.91). Originality/value: – Athletes using NS had different characteristics from non-users, and seemed to have healthier and more sports-oriented food choices. Our findings may help sport and health professionals to identify an alleged or future NS user, enabling the development of a timely and self-directed supplement scheme.